ANALISIS BAURAN PEMASARAN RITEL TERHADAP POSITIONING LOTTE MART WHOLESALE PALEMBANG (STUDI KASUS PERBANDINGAN ANTARA LOTTEMART WHOLE SALE DENGAN INDOGROSIR PALEMBANG) - Matias Andrianus S; Suhartini Karim; Dian Eka (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2013)
This research aims to determine the positioning of Lotte Mart Wholesale Palembang compared to other competitor by analyzing the result of the questionary that is already been spread towards 100 people as the respondents. Techniques of analysis is using the qualitative and quantitative techniques including validity test, reliability test, frequencies test, descriptives test, crosstab test and then look for the perception maps through correspondence analysis using SPSS for Windows version 17.0. Based on the result of correspondence analysis, it shows two superiorities owned by Lotte Mart Wholesale Palembang which affected it’s strategy of positioning, those are the price of product and location of Lotte Mart itself. Hence, positioning strategy that can be done is positioning strategy based on image differentiation. Last but not least, in order to increasing performance and competitiveness of Lotte Mart Wholesale Palembang, researcher suggesting to maintain performance of price and location indicator, also to keep comunicating those superiorities to consumers. Afterward, there is necessary to increase performance of the most important indicators before consumers, such as product quality and servicing indicator.Keywords: Positioning, Map Perception and Wholesaler.